STUDY ON THE STRUCTURAL BASIS OF PERIPHERAL LIGHT HARVESTING COMPLEXES (LH2) IN PURPLE NON-SULPHUR PHOTOSYNTHETIC BACTERIA - Tatas H.P. Brotosudarmo; Richard J. Cogdell (Universitas Gadjah Mada, 2010)
Photosynthesis provides an example of a natural process that has been optimized during evolution to harness solar energy efficiently and safely, and finally to use it to produce a carbon-based fuel. Initially, solar energy is captured by the light harvesting pigment-protein complexes. In purple bacteria these antenna complexes are constructed on a rather simple modular basis. Light absorbed by these antenna complexes is funnelled downhill to reaction centres, where light drives a trans-membrane redox reaction. The light harvesting proteins not only provide the scaffolding that correctly positions the bacteriochlorophyll a and carotenoid pigments for optimal energy transfer but also creates an environment that can modulate the wavelength at which different bacteriochlorophyll molecules absorb light thereby creating the energy funnel. How these proteins can modulate the absorption spectra of the bacteriochlorophylls will be discussed in this review.